KOMPETENSI NAKHODA KAPAL RAWAI TUNA DI PALABUHANRATU DITINJAU DARI STANDAR KOMPETENSI KERJA NASIONAL INDONESIA (SKKNI) (Competency of Tuna Longliner Captain at Palabuhanratu, Viewed From Indonesian National Working Competency Standards (SKKNI)) - Tri Wiji Nurani; Yasinta Anugerah; Muhammad Fedi A. Sondita (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2017)
ABSTRACTIndonesian government has prepared a standard for assessing the competencies of human resources in the field of fisheries, through the formulation of Indonesian National Occupational Competency Standards (INOCS). Captain of fishing vessels has an important role to the success of fishing operations, which must be supported by adequate competencies. This research aimed to describe INOCS in the field of fishing; and to assess the competence of the Captain of longline fishing vessels according to the INOCS. Data analysis was carried out by descriptive and gap analysis method. The result of the study showed that the competency of the Captain had been formulated, included five units of competencies with twenty elements of competencies. Among them, ten elements of competencies had been achieved, while the other ten competencies still had gaps. Elements of competency that has been achieved are mostly in accordance with the level V, while the level VI had not been achieved yet.Keywords: captain, competency, gap analysis, SKKNI, tuna longlineABSTRAKPemerintah Indonesia telah mempersiapkan perangkat untuk menilai kompetensi sumberdaya manusia di bidang perikanan, melalui perumusan Standar Kompetensi Kerja Nasional Indonesia (SKKNI). Nakhoda kapal penangkap ikan tuna memiliki peran penting untuk keberhasilan operasi penangkapan ikan, yang harus didukung oleh kompetensi yang memadai. Penelitian ini bertujuan untuk mempelajari SKKNI di bidang penangkapan ikan; dan menilai kompetensi Nakhoda sesuai SKKNI. Analisis dilakukan secara deskriptif dengan menggunakan analisis kesenjangan (gap).Â  Hasil penelitian menyatakan bahwa unit kompetensi nakhoda telah dirumuskan dengan baik. Terdapat lima unit kompetensi dengan dua puluh elemen kompetensi.Â  Sepuluh elemen kompetensi telah tercapai, sementara itu sepuluh elemen kompetensi lainnya masih terdapat gap. Elemen kompetensi yang sudah tercapai sebagian besar adalah sesuai dengan jenjang V, sementara itu yang belum tercapai pada jenjang VI.Kata kunci: nakhoda, kompetensi, analisis kesenjangan, SKKNI, tuna longline